Ivy league delinquency: A self-report analysis - Durham, Alexis M. (American journal of criminal justice, 1988)
Since the 1940s, self-report technology has been utilized to improve our understanding of the frequency and distribution of crime and delinquency. Findings based upon self-reports have called into question the traditional class-based view of criminality. It is now apparent that middle- and upper-class young people are involved in delinquent activity, although the precise extent and nature of such involvement remains unclear. The research detailed in this report attempts to add to our understanding of class and illegal activities by examining a sample of Ivy League undergraduates for evidence of participation in serious forms of delinquency. It can be argued that such a sample is especially interesting both because these respondents represent the “best and the brightest,” and because they possess relatively advantaged positions regarding access to conventional kinds of power and success. The findings indicate that serious delinquency is by no means rare among these youth. Involvement in violence, however, appears to be relatively infrequent and weighted toward the less serious end of the continuum of violent delinquency. In addition, the delinquent activity of this sample was highly diverse. Even for the most serious offenders the results provide little evidence of offense specialization.